Mapping Global Research Trends on Ethnoscience-Based Chemistry Learning Integrated with Project-Based Learning and Flipped Classroom to Support Sustainable Development Goals: A Bibliometric Review - Minarni; Rayandra Asyhar; Haryanto; Bambang Hariyadi (Postgraduate, University of Mataram, 2026)
This study maps global research trends on ethnoscience-based chemistry learning integrated with Project-Based Learning (PjBL) and the Flipped Classroom (FC) using a bibliometric approach. A total of 118 journal articles published between 2016 and 2025 were analyzed with VOSviewer to examine publication trends, keyword co-occurrence, and thematic clusters. Results show a significant increase in publications after 2020, highlighting five main clusters: (1) ethnoscience and local wisdom, (2) PjBL and active pedagogy, (3) FC and digital learning, (4) scientific literacy and 21st-century skills, and (5) bibliometric analysis and research trends. Overlay and density visualizations indicate a recent focus on PjBL–FC integration to enhance scientific literacy, while ethnoscience provides a contextual foundation. This study identifies gaps in fully integrated empirical research and offers directions for future studies and practical implications for curriculum design, teacher training, and sustainable learning. These findings provide actionable insights for educators and policymakers aiming to enhance culturally responsive, technology-supported chemistry education that promotes sustainable development aligned with the United Nations Sustainable Development Goals.